Nutritional and antioxidant potential of Gelidium corneum from the El Jadida coast, Morocco - Cherki, Mounia Cherki; Taouam, Ikram Taouam; Dbila, Imane Dbila; Maaloum, Mohamed El Maaloum El; Madouf, Salma Madouf; Bouqdaoui, Karima El Bouqdaoui El (Sulaimani Journal for Humanities, 2025)
Gelidium corneum is a common red macroalgae (Rhodophyta) along the Atlantic coast of Morocco, particularly in El Jadida surrounding coast areas. It is recognized for its industrial importance as an excellent-grade agar producer, but also with growing interest because of its bioactive compounds with nutritional and pharmacotherapeutic values. The goal of the current investigation is to evaluate this marine species based on its macronutrient and secondary metabolite composition and antioxidant capacity. Chemical examination of powdered algal material revealed appreciable levels of protein (26 ± 0.0007%), carbohydrate (55 ± 0.006%), and lipid (6 ± 0.001%). Our algal sample proved to be nutritionally beneficial as a consequence of its high alkaloid, flavonoid, coumarin, and tannin content.Algal biomass has dose-dependent activity towards scavenging DPPH free radicals with high antioxidant activity. G. corneum from the El Jadida region has interesting functional properties in addition to nutritional value as expressed through its macronutrient and secondary metabolite content, and thus these marine products are worthy candidates for sustainable progress in the pharmaceutical, cosmetic, and food industries.
Keywords: macronutrients; Gelidium corneum; DPPH test; antioxidant activity; secondary metabolites; Morocco